PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING DI DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA LUBUKLINGGAU - Irma Idayati; Surajiyo Surajiyo; Marvia Hazalena (LPPM UNIVERSITAS BINA INSAN, 2020)
This study entitled The Effect of Competence and Work Environment on Employee Performance through Motivation as an Intervening Variable in the Education and Culture Office of the City of Lubuklinggau. The method used in this study using a questionnaire and observation. Testing the first hypothesis, namely Variable Competence (X1) on Motivation (Z)